Chimp and Zee - Anholt, Catherine; Anholt, Laurence (New York : Phyllis Fogelman Books, 2001)
Two mischievous monkeys are separated from their mother while shopping for bananas, but remarkably end up back home.
Keywords: Monkeys -- Fiction; Missing children -- Fiction